Therapeutic lithium alters polar head-group region of lipid bilayer and prevents lipid peroxidation in forebrain cortex of sleep-deprived rats - Vošahlíková, Miroslava; Roubalová, Lenka; Brejchová, Jana; Alda, Martin; Svoboda, Petr (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Lithium is regarded as a unique therapeutic agent for the management of bipolar disorder (BD). In efforts to explain the favourable effects of lithium in BD, a wide range of mechanisms was suggested. Among those, the effect of clinically relevant concentrations of lithium on the plasma membrane was extensively studied. However, the biophysical properties of brain membranes isolated from experimental animals exposed to acute, short-term and chronic lithium have not been performed to-date. In this study, we compared the biophysical parameters and level of lipid peroxidation in membranes isolated from forebrain cortex (FBC) of therapeutic lithium-treated and/or sleep-deprived rats. Lithium interaction with FBC membranes was characterized by appropriate fluorescent probes. DPH (1,6-diphenyl-1,3,5-hexatriene) and TMA-DPH (1-(4-trimethylammoniumphenyl)-6-phenyl-1,3,5-hexatriene p-toluenesulphonate) were used for characterization of the hydrophobic lipid core and Laurdan (6-dodecanoyl-2-dimethylaminonaphthalene) for the membrane-water interface. Lipid peroxidation was determined by immunoblot analysis of 4-HNE-(4-hydroxynonenal)-protein adducts. The organization of polar head-group region of FBC membranes, measured by Laurdan generalized polarization, was substantially altered by sleep deprivation and augmented by lithium treatment. Hydrophobic membrane interior characterized by steady-state anisotropy of DPH and TMA-DPH fluorescence was unchanged. Chronic lithium had a protective effect against peroxidative damage of membrane lipids in FBC. In summary, lithium administration at a therapeutic level and/or sleep deprivation as an animal model of mania resulted in changes in rat FBC membrane properties.
Keywords: fluidita membrány; Prosencephalon; Lipid Bilayers; Sleep Deprivation; Lithium; lithium; přední mozek; membránové lipidy; peroxidace lipidů; krysa rodu Rattus; zvířata; spánková deprivace; lipidové dvojvrstvy; Male; Membrane Fluidity; Rats; Animals; mužské pohlaví; Membrane Lipids; Lipid Peroxidation